Guidelines for reasonable and appropriate care in the emergency department (GRACE): Recurrent, low‐risk chest pain in the emergency department. (6th July 2021) - Musey, Paul I.; Bellolio, Fernanda; Upadhye, Suneel; Chang, Anna Marie; Diercks, Deborah B.; Gottlieb, Michael; Hess, Erik P.; Kontos, Michael C.; Mumma, Bryn E.; Probst, Marc A.; Stahl, John H.; Stopyra, Jason P.; et al.
Abstract: This first Guideline for Reasonable and Appropriate Care in the Emergency Department (GRACE‐1) from the Society for Academic Emergency Medicine is on the topic: Recurrent, Low‐risk Chest Pain in the Emergency Department. The multidisciplinary guideline panel used The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to assess the certainty of evidence and strength of recommendations regarding eight priority questions for adult patients with recurrent, low‐risk chest pain and have derived the following evidence based recommendations: (1) for those >3 h chest pain duration we suggest a single, high‐sensitivity troponin below a validated threshold to reasonably exclude acute coronary syndrome (ACS) within 30 days; (2) for those with a normal stress test within the previous 12 months, we do not recommend repeat routine stress testing as a means to decrease rates of major adverse cardiac events at 30 days; (3) insufficient evidence to recommend hospitalization (either standard inpatient admission or observation stay) versus discharge as a strategy to mitigate major adverse cardiac events within 30 days; (4) for those with non‐obstructive (<50% stenosis) coronary artery disease (CAD) on prior angiography within 5 years, we suggest referral for expedited outpatient testing as warranted rather than admission for inpatient evaluation; (5) for those with no occlusive CAD (0% stenosis) on prior angiography within 5 years, we recommend referral for expedited outpatient testing as warranted rather than admission for inpatient evaluation; (6) for those with a prior coronary computed tomographic angiography within the past 2 years with no coronary stenosis, we suggest no further diagnostic testing other than a single, normal high‐sensitivity troponin below a validated threshold to exclude ACS within that 2 year time frame; (7) we suggest the use of depression and anxiety screening tools as these might have an effect on healthcare use and return emergency department (ED) visits; and (8) we suggest referral for anxiety or depression management, as this might have an impact on healthcare use and return ED visits.